Obsession in Death : In Death #40 - Robb, J. D., 1950- (New York : Putnam, 2015)
Police lieutenant Eve Dallas must contend with an admirer who is killing innocent people to prove his devotion.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- Fiction; Murder -- Investigation -- Fiction; Dallas, Eve (Fictional character) -- Fiction; Policewomen -- New York (N Y ) -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction